Out in Front: Government Regulation of Television in Malaysia: Government Regulation - Kitley, Philip; Nain, Zaharom (Television, Regulation and Civil Society in Asia, 2002)
Modern Malaysia was established in 1963 following a drawn-out struggle against British interests which had occupied territory on Penang and Singapore and the Straits of Malacca in 1786, 1819 and 1824 respectively. In 1867 these outposts came under the control of the British Colonial Office and were governed as a Crown Colony. Although Britain did not directly colonise the Malay States, which remained legally autonomous, it imposed effective administrative control over Malaya and the Borneo territories from the late 1870s until the Japanese occupation in 1942.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Malaisie (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Televised Journalistic Documentaries of the 1990s: The Form, Content, and Historical Juncture - Çelik, Burçe (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The 1990s’ popular televised journalistic/history documentaries have played a vital role in the making of political television culture, society of political spectacle, and the production of popular history and memory in Turkey. Despite their importance, these documentaries did not attract enough scholarly attention. By focusing on arguably the most popular and impactful journalistic/history documentaries of Turkey’s history, developed by Mehmet Ali Birand in the 1990s, I will assess the role of television in teaching, telling, and writing the political history. In doing so, I will also contextualize the form and discourse of these documentary series within historical juncture of globalization and neoliberalization of television as well as the country’s political economy.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Paradoxale légitimation culturelle du jeu vidéo - Derfoufi, Mehdi (De l'autre côté, 2019)
Qualifié parfois de « dixième art », après que les jeux de rôles sur table (comme Donjons & Dragons) eurent commencé à céder du terrain dans les loisirs de la jeunesse à partir du mil…
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Gender, Race, and Class in Media a Critical Reader - Dines, Gail.; Humez, Jean M. (SAGE Publications, 2015)
Incisive analyses of mass media - including such forms as talk shows, MTV, the Internet, soap operas, television sitcoms, dramatic series, pornography, and advertising-enable this provocative third edition of Gender, Race and Class in Media to engage students in critical mass media scholarship. Issues of power related to gender, race, and class are integrated into a wide range of articles examining the economic and cultural implications of mass media as institutions, including the political economy of media production, textual analysis, and media consumption. Throughout, Gender, Race and Class in Media examines the mass media as economic and cultural institutions that shape our social identities, especially in regard to gender, race, and class.
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave games in context, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."--Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play -- the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gameplay in the “Zone of Becoming”: Locating Action in the Computer Game - Mukherjee, Souvik (Conference Proceedings of The Philosophy of Computer Games 2008, 2009)
Extending Alexander Galloway’s analysis of the action-image in videogames, this essay explores the concept in relation to its source: the analysis of cinema by the French philosopher Gilles Deleuze. The applicability of the concept to videogames will, therefore, be considered through a comparison between the First Person Shooter S.T.A.L.K.E.R. and Andrey Tarkovsky’s film Stalker. This analysis will compellingly explore the nature of videogame-action, its relation to player-perceptions and its loca-tion within the machinic and ludic schema.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé